More than Mycobacterium tuberculosis: site-of-disease microbial communities, and their functional and clinical profiles in tuberculous lymphadenitis. Issue 3 (8th December 2022) - Nyawo, Georgina R; Naidoo, Charissa C; Wu, Benjamin; Sulaiman, Imran; Clemente, Jose C; Li, Yonghua; Minnies, Stephanie; Reeve, Byron W P; Moodley, Suventha; Rautenbach, Cornelia; Wright, Colleen; Singh, Shivani; et al.
Abstract : Background: Lymphadenitis is the most common extrapulmonary tuberculosis (EPTB) manifestation. The microbiome is important to human health but uninvestigated in EPTB. We profiled the site-of-disease lymph node microbiome in tuberculosis lymphadenitis (TBL). Methods: Fine-needle aspiration biopsies were collected from 158 pretreatment presumptive TBL patients in Cape Town, South Africa. 16S Illumina MiSeq rRNA gene sequencing was done. Results: We analysed 89 definite TBLs (dTBLs) and 61 non-TBLs (nTBLs), which had similar α- but different β-diversities (p= 0.001 ). Clustering identified five lymphotypes prior to TB status stratification: Mycobacterium- dominant, Prevotella- dominant and Streptococcus- dominant lymphotypes were more frequent in dTBLs whereas a Corynebacterium -dominant lymphotype and a fifth lymphotype (no dominant taxon) were more frequent in nTBLs. When restricted to dTBLs, clustering identified a Mycobacterium -dominant lymphotype with low α-diversity and non- Mycobacterium -dominated lymphotypes (termed Prevotella-Corynebacterium, Prevotella-Streptococcus ). The Mycobacterium dTBL lymphotype was associated with HIV-positivity and features characteristic of severe lymphadenitis (eg, larger nodes). dTBL microbial communities were enriched with potentially proinflammatory microbial short-chain fatty acid metabolic pathways (propanoate, butanoate) vs nTBLs. 11% (7/61) of nTBLs had Mycobacterium reads BLAST-confirmed as Mycobacterium tuberculosis complex. Conclusions: TBL at the site-of-disease is not microbially homogeneous. Distinct microbial community clusters exist that, in our setting, are associated with different clinical characteristics, and immunomodulatory potentials. Non- Mycobacterium -dominated dTBL lymphotypes, which contain taxa potentially targeted by TB treatment, were associated with milder, potentially earlier stage disease. These investigations lay foundations for studying the microbiome's role in lymphatic TB. The long-term clinical significance of these lymphotypes requires prospective validation.